Age, but Not Amyloidosis, Induced Changes in Global Levels of Histone Modifications in Susceptible and Disease-Resistant Neurons in Alzheimer’s Disease Model Mice - Dyer, Marcus; Phipps, Andrew J.; Mitew, Stanislaw; Taberlay, Phillippa C.; Woodhouse, Adele (Frontiers in Aging Neuroscience, 2019)
There is increasing interest in the role of epigenetic alterations in Alzheimer’s disease (AD). The epigenome of every cell type is distinct, yet data regarding epigenetic change in specific cell types in aging and AD is limited. We investigated histone tail modifications in neuronal subtypes in wild-type and APP/PS1 mice at 3 (pre-pathology), 6 (pathology-onset) and 12 (pathology-rich) months of age. In neurofilament (NF)-positive pyramidal neurons (vulnerable to AD pathology), and in calretinin-labeled interneurons (resistant to AD pathology) there were no global alterations in histone 3 lysine 4 trimethylation (H3K4me3), histone 3 lysine 27 acetylation (H3K27ac) or histone 3 lysine 27 trimethylation (H3K27me3) in APP/PS1 compared to wild-type mice at any age. Interestingly, age-related changes in the presence of H3K27ac and H3K27me3 were detected in NF-labeled pyramidal neurons and calretinin-positive interneurons, respectively. These data suggest that the global levels of histone modifications change with age, whilst amyloid plaque deposition and its sequelae do not result in global alterations of H3K4me3, H3K27ac and H3K27me3 in NF-positive pyramidal neurons or calretinin-labeled interneurons.